2009
DOI: 10.1186/bcr2361
|View full text |Cite
|
Sign up to set email alerts
|

Key signalling nodes in mammary gland development and cancer. Mitogen-activated protein kinase signalling in experimental models of breast cancer progression and in mammary gland development

Abstract: Seven classes of mitogen-activated protein kinase (MAPK) intracellular signalling cascades exist, four of which are implicated in breast disease and function in mammary epithelial cells. These are the extracellular regulated kinase (ERK)1/2 pathway, the ERK5 pathway, the p38 pathway and the c-Jun N-terminal kinase (JNK) pathway. In some forms of human breast cancer and in many experimental models of breast cancer progression, signalling through the ERK1/2 pathway, in particular, has been implicated as being im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 180 publications
(222 reference statements)
5
130
0
3
Order By: Relevance
“…The observations in the present study indicate that activation of p38 is EGFR-dependent in Cr(VI)-transformed cells. Activation of p38 has been shown to correlate with increased tumor malignancy and poor prognosis of cancer patients (39,40). Although hypoxia up-regulates HIF-1␣ through p38 in various cells (41), it has been reported that activation of p38 by hypoxia is mediated by HIF-1␣ in human hepatoma BEL-7405 cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…The observations in the present study indicate that activation of p38 is EGFR-dependent in Cr(VI)-transformed cells. Activation of p38 has been shown to correlate with increased tumor malignancy and poor prognosis of cancer patients (39,40). Although hypoxia up-regulates HIF-1␣ through p38 in various cells (41), it has been reported that activation of p38 by hypoxia is mediated by HIF-1␣ in human hepatoma BEL-7405 cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…The association of a high JNK signature in ER 1 /HER2 2 ("luminal" subtype) breast cancers is also consistent with reports from previous clinical studies and xenograft models of tamoxifen resistance, which have reported a positive association with activated/phosphorylated JNK ( Johnston et al 1999;Schiff et al 2000), although these tumors do not show high expression of the Ras signature ( Figure 7E). While Ras is not an established oncogene in breast cancer, Ras pathway upregulation is recognized to be important for breast cancer growth and tumorigenesis (reviewed by Whyte et al 2009), and our data support a link between Ras and JNK signaling in HER2 1 breast cancers. Together these data support further investigation into the relationship between JNK and Ras signaling in human cancers.…”
Section: Uas-pbl-gfp#8supporting
confidence: 52%
“…Further, high glucoseinduced phosphorylation of p38 in human endothelial cells leads to cell death (Nakagami et al 2001). ERK1/2 activity is associated with invasive and metastatic properties (Whyte et al 2009); its activation results in desensitization of pore opening and increased resistance to death stimuli, providing advantage to tumor cells (Rasola et al 2010). Our results show that cellular stress under a high-glucose condition in MCF-7 cells results in activation of p38 and de-phosphorylation of ERK, thereby leading to cell death.…”
Section: Discussionmentioning
confidence: 79%